1983
DOI: 10.1016/0014-5793(83)81115-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid purification of bovine kidney branched‐chain 2‐oxoacid dehydrogenase complex containing endogenous kinase activity

Abstract: Branched-chain 2-oxoacid dehydrogenase compIex has been purified to near homogeneity by a simple, rapid procedure. The final product contains endogenous kinase activity capable of phosphorylating and inactivating the compIex. Phosphorylation continues after complete inactivation, indicating the possibility of several phosphorylatabte sites.Branched-chain 2-oxoacid dehydrogenase complex Rapid purification Inactivation (Bovine kidney cortex) Phosphorylation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…PDC and OGDC were purified from bovine heart as in refs. 25 and 26, whereas BCOADC was purified from bovine kidney (27). The E2 (+X) component of PDC and E2 of BCOADC were obtained by resolution of the respective complexes, using gel filtration on Superose 6 (Pharmacia) in the presence of 1 M NaCI (28), as was an E1-E2 subcomplex of OGDC.…”
Section: Methodsmentioning
confidence: 99%
“…PDC and OGDC were purified from bovine heart as in refs. 25 and 26, whereas BCOADC was purified from bovine kidney (27). The E2 (+X) component of PDC and E2 of BCOADC were obtained by resolution of the respective complexes, using gel filtration on Superose 6 (Pharmacia) in the presence of 1 M NaCI (28), as was an E1-E2 subcomplex of OGDC.…”
Section: Methodsmentioning
confidence: 99%
“…Complex was phosphorylated as described in Lawson et al (1983) (Cook et al, 1984) to be present on the a-subunit (results not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Branched-chain 2-oxo acid dehydrogenase was purified and assayed as described by Lawson et al (1983). Complex was phosphorylated as described in Lawson et al (1983) (Cook et al, 1984) to be present on the a-subunit (results not shown).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6) In the early 1980 s, several reports regarding BCKDC purification from various animal tissues were published. [7][8][9][10] In addition, nearly two decades ago, we too reported a novel procedure for the purification of BCKDC from frozen rat liver. 3,11) In those reports, we described a phenyl-Sepharose-based hydrophobic interaction chromatography method that yielded highly purified BCKDC.…”
mentioning
confidence: 99%